ANALISIS STRUKTUR INTRINSIK PADA NOVEL BYAR-BYUR RING PESISI SANUR KARYA NYOMAN - Ni Putu Eka Arya Suci Ratna Dewi; I Gusti Agung Rai Jayawangsa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
In general, this research aims to develop the love of Balinese people for Balinese literature. Specifically, this study aims to analyze the intrinsic structure in Novel Biyar - Biyur ring Pasisi Sanur. In this study, it can be concluded that the intrinsic structure analysis of the novel Biyar - Biyur ring Pasisi Sanur is the theme of heroism, with characters including I Wayan Sadia, Luh Renji, Kwee Tek Tjiang. With the characterization of this character, Wayan Sadia is diligent, Luh Renji is right about his promise, Kwee Tek Tjiang is cunning. The flow used is a straight line (progressive) with a background in 1904 and a place in the village of Sanur. The mandate that was obtained was to be careful of foreigners and fulfill the task of defending the country from invadersKeywords: Analysis, Intinsic Structure, Novel Byar-Byur di Pesisi Sanur